Crescent City Girls : The Lives of Young Black Women in Segregated New Orleans - Simmons, LaKisha Michelle (Book collections on Project MUSE., 2016)
What was it like to grow up black and female in the segregated South? To answer this question, LaKisha Simmons blends social history and cultural studies, recreating children's streets and neighbourhoods within Jim Crow New Orleans and offering a rare look into black girls' personal lives.